Persepsi Orang Tua tentang Kesiapan Anak Memasuki Sekolah Dasar dalam Teori Kognitif Vygotsky - Marini, Tria; Fitri, Fitri; Nusir, Lidia; Laila, Misbah (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
Perceptions of readiness for elementary school are parents' views, understanding, and assessments of their children's abilities, such as cognitive, social-emotional, language, motor, and independence aspects. The purpose of this study is to explore parents' perceptions of their children's readiness for elementary school, focusing on the differences in perceptions between fathers and mothers in one family and exploring the cognitive abilities of children. This study uses a case study approach, with the research subject being the parents of an 8-year-old boy with the initials RD. Data was collected through in-depth interviews, observation, and documentation. The results show that there are differences in perception between RD's father and mother regarding the child's readiness to enter elementary school. These differences in perception are influenced by three factors, namely (1) each parent's understanding of the concept of school readiness, (2) their personal experiences in undergoing education in the past, and (3) their expectations for RD's future education. The findings of this study are that parents' perceptions of their children's readiness to enter elementary school are subjective and influenced by internal and social factors, and that open communication and collaboration between parents in making decisions about their children's education are important. RD is a gifted child with academic abilities above the average of his peers. RD's discomfort and demotivation in elementary school arose because his learning needs as a gifted child were not optimally met in a regular school environment.